Electrochemical detection of the antiprotozoal drug dimetridazole using κ-carrageenan functionalized gadolinium tin oxide nanoparticles. Issue 3 (June 2022) - Selvi, Subash Vetri; Jayachitra, Ravichandran; Lincy, Varghese; Prasannan, Adhimoorthy; Hong, Po-Da
Abstract: Dimetridazole (DMZ) is an antimicrobial drug used to treat bacterial and protozoan infections in humans and poultry farms. An excessive dosage of DMZ can be life-threatening, as it has carcinogenic effects. Hence, ensuring that DMZ remains at a very low level in the environment is essential for day-to-day human life. Herein, we report the development of a novel biocomposite using κ-carrageenan (κ-CGN) functionalized with gadolinium tin oxide nanoparticles (NPs), κ-CGN/GdSnO2 NPs, for the effective electrochemical detection of DMZ. The biocomposites, κ-GCN/GdSnO2 NPs, were successfully synthesized by the sonochemical method, and their structural features were evaluated using various spectroscopic and microscopic techniques. A glassy carbon electrode was coated with the synthesized κ-CGN/GdSnO2 NPs, it was used as an electrode surface modifier material for the detection of DMZ, and it exhibited excellent electrocatalytic activity. In addition, the modified electrode showed many advantages, such as a lower detection limit (3.1 nM), wide linear range (0.019–708.8 µM), good sensitivity (0.62 µA µM −1 cm −2 ), and high selectivity in the presence of co-interfering species. The designed κ-CGN/GdSnO2 NPs-based composite material can contribute to outstanding sensor performance in aquatic samples because of its repeatability, reproducibility, storage stability, and satisfactory accuracy. Therefore, κ-CGN/GdSnO2 NPs could be used to develop potential electrode modifier materials for electrochemical sensor applications and to detect toxic components, such as DMZ, in environmental aquatic samples. Graphical Abstract: ga1 Highlights: The κ-Carrageenan functionalized – gadolinium tin oxide nanoparticles was synthesized by sonochemical method for GCE modification. The electrocatlytic reduction of dimetridazole was conducted with κ-CGN/GdSnO2 NPs. The lower limit of detection 3.1 nM with the good linear range 0.019–708.8 µM. Fabricated sensors (κ-CGN/GdSnO2 NPs) exhibited the high performance of DMZ detection in environmental sample.